Sosialisasi dan pelatihan Pembuatan Sabun Mandi menggunakan Hasil Bumi Desa Aik Bukaq - Rosadi, Narita Amni; Amnesty, Lara; Hardi, M. Jaya; Delasintia, Nisa; Wahyudin, Pahmi (Jurnal Pengabdian Masyarakat Nusantara (JPMN), 2024)
Aik Bukaq Village is one of the villages rich in natural resources such as coconuts, herbal plants, and essential oils. However, this potential has not been fully utilized to improve the community's economy. To overcome this, socialization and training were carried out on making natural-based bath soap from village agricultural products. This activity aims to empower the community by providing knowledge and skills in making bath soap with high economic value. The methods used in this training include three main stages: socialization, demonstration, and direct practice. At the socialization stage, participants are given an understanding of the importance of utilizing local resources for value-added products. At the demonstration stage, the instructor shows how to make bath soap with coconut oil, essential oils, and other natural ingredients available in Aik Bukaq Village. Furthermore, at the direct practice stage, participants are invited to practice the soap-making process themselves, starting from mixing ingredients, printing, to product packaging. The results of this training show that participants are able to produce good quality bath soap, and understand the overall production process. Several bath soap products produced have a distinctive aroma from local essential oils, which is an additional selling point. In addition, this training also succeeded in increasing public awareness of the economic potential of utilizing local agricultural products. In the future, it is hoped that participants can produce soap independently and make it one of the village's superior products that can be marketed more widely. Thus, this activity not only improves community skills but also contributes to improving economic welfare in Aik Bukaq Village.